Copaifera langsdorffii Desf. (Fabaceae) potential as an indicator of climate change by tree ring analysis, Parana, Brazil - Miranda, Bruno Palka; Andrade, Victor Hugo Ferreira; Botosso, Paulo Cesar; Santos, Tomaz Longhi; Milani, Jaçanan Eloisa de Freitas; Roderjan, Carlos Vellozo (Revista de Ciências Agroveterinárias, 2019)
Under the current issue of climate change, having access to tools that allow its analysis has become essential for the correct understanding of such changes. The interpretation of climatic signals evidenced in tree rings is one of the ways to understand these relations. Therefore, this study aimed to evaluate how regional climatic relationships have an effect on the Copaifera langsdorffii growth rings, a typical species of the seasonal semideciduous forests of Parana. We used four trees as a result of the vegetation suppression to form the reservoir of the Jayme Canet Júnior Hydroelectric Power Plant, in the middle portion of the Tibagi River, between the municipalities of Telemaco Borba and Ortigueira. From the cross sections of the trees, 40 series were drawn in order to identify and demarcate the limits of the growth rings. Then, we measured the width of the growth rings and performed a quality control and the construction of a regional chronology for the species. The climatic data used for these correlations were obtained from the official meteorological institutes of Parana and a global climate database. The chronology has 240 years, with significant intercorrelation (r = 0,469, p <0.01). The relationship between development peaks and El Niño events was identified, with positive correlations from the 1970s, especially in 1983 (strongest El Niño in Southern Brazil). In this way, the preliminary results reinforce this species potential to be used for dendroecological studies, which may also help in the understanding of climatic changes, as well as their effects at a regional and local level, when incorporated into a sample universe of greater representativity.